The germinal centre reaction and follicular T cells in alloantibody formation - Wallin, E (2016)
Kidney transplantation is the optimal treatment for end-stage renal failure, however graft lifespan remains limited, and a major cause of graft loss is chronic, low-grade antibody-mediated damage. Understanding more about how these antibodies are produced, and how immunosuppression affects cells producing them, may allow both prediction of those at risk, and a mechanism for preventing or minimising antibody production, therefore improving graft lifespan. In particular, interest has grown in CD4 T cells known as circulating T follicular helper (cTfh) and T follicular regulatory (cTfr) cells, which appear to correlate with antibody production in vaccination, autoimmunity and potentially transplantation, however little is known about how immunosuppression alters these cells and their function. This study aimed to establish whether cTfh and cTfr cells could be used to predict the risk of de novo donor-specific antibody (DSA) formation in 61 kidney and simultaneous pancreas kidney (SPK) transplant recipients. Results suggested that high cTfh cells and low cTfr associated with de novo DSA formation, and the ratio of the two cells may be useful for identifying at-risk patients. Different immunosuppression regimens were associated with different levels of risk for de novo DSA formation, with basiliximab induction combined with azathioprine maintenance therapy having the lowest risk, despite being considered a less intensive regimen. In vitro experiments suggest this may be due to a differential effect of azathioprine on cTfh and B cells compared to mycophenolate mofetil, an alternative maintenance agent. Combining the in vitro and clinical data suggests that azathioprine may reduce the risk of de novo DSA formation after transplantation compared to other agents because of its effects on B cells, cTfh and cTfr. This is an exciting development that warrants further investigation.